Review: Alexey V. Belousov, Defixiones Olbiae Ponticae, Peeters, Leuven [Colloquia Antiqua. Supplements to the Journal Ancient West & East 30] - Sofia ANDREEVA (Journal of Ancient History and Archaeology, 2022)
Review: Alexey V. Belousov, Defixiones Olbiae Ponticae, Peeters, Leuven [Colloquia Antiqua. Supplements to the Journal Ancient West & East 30], 2021, 124 p., ISBN 978-90-429-4295-0; eISBN 978-90-429-4296-7.